IMPLEMENTATION OF THE FINITE ELEMENT METHOD IN SOLIDWORKS TO OPTIMIZE THE FRONT CAST WHEEL DESIGN FOR MOTORCYCLES - Rizki Nur Afami Kurniawan; Dedik Romahadi; Muhamad Fitri; Md Radwanul Karim (Universitas Mercu Buana, Prodi S2 Teknik Mesin, 2022)
Cast wheel rims often experience damage that causes damage to the lip of the rim, or the spokes rupture if it supports the excessive load. The safety aspect is very important to be considered in the automotive industry because it involves the lives of passengers. Structural optimization of various vehicle components has shown that component weight strongly influences vehicle performance. Based on these problems, this research aims to design a lightweight cast wheel design model that can withstand a load of 535 N. So, it is necessary to make an analysis using a comparison of design models and material variations and static simulations using Solidworks 2018 software. The results sought are von mises, displacement, strain, a factor of safety, and produce a lightweight design. The simulation results on the three models are still safe in holding a load of 535 N because the value of the factor of safety is not less than 1. The results of the design mass with material variations are lighter than the original wheels.